Tourism Forecasting: Accuracy of Alternative Econometric Models Revisited - Haiyan Song; Egon Smeral; Gang Li; Jason L. Chen (Austrian Institute of Economic Research (WIFO), 2008)
This study evaluates the forecasting accuracy of five alternative econometric models in the context of predicting the quarterly international tourism demand in 25 countries or country groupings. Tourism demand is measured in terms of tourist expenditure by inbound international visitors in a destination. Two univariate time series models are included in the forecasting comparison as benchmarks. Accuracy is assessed in terms of error magnitude. Seasonality is an important feature of forecasting models and requires careful handling. For each of the 25 destinations, individual models are estimated over the 1980Q1-2005Q1 period, and forecasting performance is assessed using data covering the 2005Q2-2007Q1 period. The empirical results show that the time-varying parameter (TVP) model provides the most accurate short-term forecasts, whereas the naïve (no-change) model performs best in long-term forecasting up to two years. This study provides new evidence of the TVP model's outstanding performance in short-term forecasting. Through the incorporation of a seasonal component into the model, the TVP model forecasts short-run seasonal tourism demand well.
Keywords: 330; tourism forecasting; econometric models; time series models; forecasting accuracy; Urlaubsverhalten; Gesamtwirtschaftliche Nachfrage; Prognoseverfahren; Zeitreihenanalyse; Modellierung; Schätzung; Welt